2020
DOI: 10.1155/2020/6101838
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cellular Reactive Oxygen Species by Activation of the EP2 Receptor Contributes to Prostaglandin E2-Induced Cytotoxicity in Motor Neuron-Like NSC-34 Cells

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating motor neuron disease characterized by progressive degeneration of motor neurons in the central nervous system. Prostaglandin E2 (PGE2) plays a pivotal role in the degeneration of motor neurons in human and transgenic models of ALS. We have shown previously that PGE2 directly induces neuronal death through activation of the E-prostanoid (EP) 2 receptor in differentiated NSC-34 cells, a motor neuron-like cell line. In the present study, to clarify the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Nevertheless, the treatment with PGE 2 for 7 days resulted in a drastic decrease in cell viability. Our laboratory has previously reported that PGE 2 induced cell death in differentiated NSC-34 cells [ 13 , 14 , 23 ]. Therefore, the PGE 2 -induced cell death observed in this study was considered to be consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the treatment with PGE 2 for 7 days resulted in a drastic decrease in cell viability. Our laboratory has previously reported that PGE 2 induced cell death in differentiated NSC-34 cells [ 13 , 14 , 23 ]. Therefore, the PGE 2 -induced cell death observed in this study was considered to be consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…The cell viability of NSC-34 cells was determined by an LDH assay using an LDH-Cytotoxic Test Wako, as previously described [ 20 , 23 ]. LDH release was assessed according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The Western blot analysis was performed as described previously [26,27]. Briefly, NSC-34 cells were lysed in a radioimmunoprecipitation buffer containing 150 mM NaCl, 1% Nonidet P-40, 0.5% sodium deoxycholate, 0.1% SDS, 50 mM Tris-HCl (pH 8.0), 1% Triton X-100, 5 mM EDTA, phosphatase inhibitor (Sigma-Aldrich, St. Louis, MO, USA), and protease inhibitor cocktail (Roche, Basel, Switzerland).…”
Section: Western Blottingmentioning
confidence: 99%
“…The amount of viable and dead cells was measured by LIVE/DEAD ® Viability/Cytotoxicity Kit for mammalian cells (Molecular Probes, Eugene, OR, USA) according to a previously described method [27]. The images were collected with an inversed fluorescence microscope (IX70, Olympus, Tokyo, Japan) and cell mortality was determined by calculating the percentage of EthD-1-positive cells of the total number of cells (the sum of calcein-positive live cells and EthD-1-positive dead cells).…”
Section: Live/dead Assaymentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is an incurable chronic neurological disease that can lead to the continuous death of upper and lower motor neurons, resulting in muscle atrophy and fatigue that affect the patient's limb movement until the death of the patient [1][2][3][4]. This disease is most likely to occur in middle-aged people, with an incidence rate of 1.5-2.7 per 100,000 people observed; in addition, most patients die within 5 years after the onset of the disease, which has a severe impact on the physical and mental health of patients [1,5,6].…”
Section: Introductionmentioning
confidence: 99%